Conversion between the local magnitude (ML) and the moment magnitude (Mw) for earthquakes in the Croatian Earthquake Catalogue - Herak, Marijan (2020)
Based on 153 earthquakes (1959–2020) listed in the Croatian Earthquake Catalogue, a conversion relation was obtained between the local magnitude ML,CR and the corresponding moment magnitude Mw as reported by the global and regional agencies. As errors were present in both variables the York regression was used. The best fit line is given by: MwL = (–0.106 ± 0.122) + (1.002 ± 0.027) ML,CR (coefficient of determination R2 = 0.90). The earthquakes considered occurred in Croatia and the neighbouring regions, and their local magnitudes ML,CR ranged between 3.5 and 6.5. Residual analysis suggests that an artificial positive magnitude shift of up to 0.3 magnitude units may have occurred in the early 1980s, when Wiechert mechanical seismographs were replaced by the instruments with velocity proportional recordings without proper recalibration of the magnitude formula. The slope of the regression close to 1.0 indicates that on the average the faults’ aspect ratio (width/length) is about 1/2.
Na temelju podataka o lokalnoj magnitudi (ML,CR) iz Hrvatskog kataloga potresa, izvedena je konverzijska relacija između ML,CR i momentne magnitude Mw koju su za odabrane potrese javile svjetske i regionalne agencije. Odabrana je tzv. Yorkova regresija koja je prikladna u slučaju da su mjerne pogreške prisutne kod obje varijable. Najbolju prilagodbu postiže se relacijom MwL = (–0,106 ± 0,122) + (1,002 ± 0,027) ML,CR (uz koeficijent determinacije R2 = 0,90). Odabrani potresi dogodili su se u Hrvatskoj i susjednim područjima, a imali su lokalne magnitude između 3,5 i 6,5. Analiza odstupanja ukazuje na mogućnost da se u katalogu početkom 1980-ih dogodio umjetni pozitivni skok u magnitudi ML,CR od ne više od 0,3 jedinice magnitude. Do njega je vjerojatno došlo pri zamjeni Wiechertovih seizmografa elektromagnetskima bez adekvatne korekcije magnitudne formule. Nagib pravca regresije vrlo blizak jedinici ukazuje da je prosječni omjer kraće i dulje stranice uzročnih rasjeda oko 1/2.
Bibliografija: str. 206-207.
Summary ; Sažetak.
Keywords: Potresi -- Magnituda potresa -- Lokalna magnituda -- Momentna magnituda; Hrvatska